Lava flow hazard assessment on Bioko Island (Equatorial Guinea) - A probabilistic approach using Q-LavHA - Jacob Brauner; Magdalena O. Chevrel; Thomas R. Walter; Oscar A.N. Ela; Christine R. Sealing; Loÿc Vanderkluysen (Volcanica)
Lava is the primary volcanic hazard on basaltic volcanoes, such as those of Bioko Island (Equatorial Guinea). The last eruption on Bioko occurred in 1923, and current emissions of CO2 indicate the presence of magma at depth and the potential for future activity. Yet, lava flow hazards associated with these volcanoes have not been assessed. Using the probabilistic Q-LavHA model, we create a series of lava hazard maps based on a TanDEM-X (TDX) digital elevation model (DEM). To confine the flow length parameter, we map six lava flows, ranging from 1.9 to 4 km in length. We locate the most likely source of the 1923 lava flow, which had an approximate length of 12 km. We constrain the height parameter through field observations to 2-8 m. Based on 437 mapped vents, we calculate a kernel density estimation and use it to weight the probability of vents opening in a given location. The highest vent opening probabilities coincide with increased lava inundation probabilities and are located along the volcanoes’ main rift zones, where the highest density of existing lava sources are found (e.g., cinder cones). Important infrastructure, including the capital city of Malabo, are mostly located in coastal areas with relatively low lava inundation probabilities. Simulated lava pathways follow erosional incisions, with a channeling effect that becomes less pronounced with increasing flow thickness. Simulated lava flows are often redirected by structural features such as the summit graben at Pico Basile.